Programmable seconds-to-days-long delayed snapping in jumping metashells - Haitao Qing; Caizhi Zhou; Fangjie Qi; Jie Yin (Proceedings of the National Academy of Sciences, 2025)
Shape-shifting structures can transform and recover their shapes in response to external stimuli, but they often lack programmable, clock-like control over spatiotemporal deformation and motion, especially after stimuli are removed. Achieving autonomous, time-regulated spatiotemporal motion remains a grand challenge. Here, we present an autonomous delayed-jumping metashell that integrates viscoelastic materials with monostable architected structures to address this limitation. The metashell with tunable prestored elastic energy features an internal time clock enabling programmable autonomous delayed snapping and jumping after actuation removal. The delay spans from seconds to 2.4 d, with jumping heights decreasing from over 9 to 0.5 body heights. We demonstrate its utility in autonomous explosive seed dispersal devices, achieving wide-area omnidirectional distribution with high survival rates. This strategy paves the way for creating autonomous spatiotemporal shape-shifting structures with broad applications in robotics, morphing matter, ecology, and intelligent systems.